Xây dựng khung lí thuyết về rào cản trong tiếp cận giáo dục đại học của người dân các tỉnh miền núi phía Bắc Việt Nam - Nguyễn Thu Hà; Trần Thị Phương Nam; Đào Thanh Hải; Triệu Thị Linh; Phạm Thị Thanh Hải (Tạp chí Giáo dục, 2026)
To construct a theoretical framework on barriers to higher education access among residents of the Northern Mountainous provinces of Vietnam, this study conducted a comprehensive literature search across online databases, combined with manual screening of reference lists, to identify relevant studies. In total, from more than 15.400 retrieved documents, 10 representative studies were screened out for in-depth analysis. The analysis results show that barriers to higher education access can be broadly classified into three main groups: (1) situational barriers; (2) institutional barriers; and (3) dispositional (personal) barriers. Building on the foundational models of Cross (1981) and Potter and Alderman (1992), and incorporating the lens of Cultural Capital Theory (Bourdieu & Passeron, 1977), the study proposes an integrative analytical framework comprising four components, adding a contextual-demographic factor to align with the ethnic, linguistic, and geographic specificities of Vietnam's Northern Mountainous region, a core distinction from the original foundational models, thereby providing a scientific basis for designing empirical studies and proposing policy interventions to promote educational equity.